Curcuma and Honey Increases Body Weight of Toddler - Renny F; Yuni Sufyanti Arief; Ni Ketut Alit Armini (Universitas Airlangga, 2010)
Introduction: Toddler may have poor appetite and picky eater stage. It will influence the children food intake and thereby they loss weight. As a result they may get a growth and developmental disorder. Curcuma honey can increase appetite and influence body weight. The purpose of this study was to analyze the influence of giving curcuma honey in increasing body weight in toddler.Methods: Quasy experimental design was used in this study. Sample was 10 toddlers and divided into two groups. Independent variable was the giving of curcuma honey and dependent variable was the increase of body weight in toddler (1–3 years). Data were collected by appetite and bodyweight observation and analyzed using paired t-test and independent t-test with significance level ofα ≤ 0.05.Results: Result showed that the giving of curcuma honey had a significant effect to increase toddler’s body weight (p = 0.001).Conclusion: It can be concluded that curcuma honey could increase body weight of toddler by increasing the toddler’s appetite. Honey contains high level of glucose and fructose that can help digestion proccess and curcuma contains curcuminoid and asiri oil that help the work of the bile and pancreas, that made the increasing in apetite and fi nally the increasing in body weight.